Modification of black glutinous rice (Oryza Sativa var. glutinosa) starch: effect on pharmaceutical properties - Devi Ratnasari; Jekmal Malau; Dhavina Maharani (Universitas Ahmad Dahlan, 2026)
Black glutinous rice is rich in starch, specifically amylopectin by 92-98%, making it a potential pharmaceutical excipient. However, black glutinous rice starch also has disadvantages, such as poor flowability and compressibility, which necessitate modification. This study investigates the impact of various modification methods on the pharmaceutical properties of black glutinous rice starch, including its Carr’s index, flowability, loss on drying, pH, and swelling power. The starches were modified using acetylation, butanol addition, autoclave-cooling, and pregelatinization. The results showed that modified butanol and pregelatinization exhibited increases in Carr’s index, 3.4 ± 0.13% and 31.10 ± 0.18%, respectively, indicating improved compressibility. Flow rate analysis revealed that pregelatinized starch exhibited the highest flowability, followed by autoclave-cooling, butanol, and acetylated starch. The swelling power was significantly enhanced in autoclave-cooled starch (100%), likely due to structural changes induced by high-temperature treatment, increasing water absorption. The pH values of all modified starches remained within pharmaceutically acceptable ranges (4–8). Overall, starch modification, particularly autoclaving and pregelatinization, significantly enhanced the functional properties relevant to pharmaceutical applications, highlighting their potential use as excipients in solid dosage forms.